Edukasi Etnokultural di NTT: Tinjauan Terhadap Tradisi Sopi dalam Penguatan Pendidikan Karakter Berbasis Kearifan Lokal di Nusa Tenggara Timur - Salamah, Nona; Yanti, Risma; Almujab, Saiful (Pimpinan Cabang Muhammadiyah Kramat Jati, 2025)
This article discusses the role of the sopi tradition in strengthening character education for students in local wisdom-based schools in East Nusa Tenggara (NTT). Through a qualitative approach using literature review methods, this research explores the ethnocultural values embedded in the sopi tradition, as well as how these values can be integrated into the education curriculum to build student character. The findings indicate that the sopi tradition not only functions as a cultural symbol but also serves as a means to teach important moral, social, and spiritual values for the development of students' character. This research is expected to provide insights for educators and policymakers in designing character education that is relevant to the local cultural context.